THE FATWA OF THE COUNCIL OF INDONESIAN ULAMA ON INTER-RELIGIOUS MARRIAGE - Lukman Yasin, R. Cecep (DE JURE, 2012)
The Qur’anic text states that it is lawful to marry women from among the People of the Book, while in the prophetic tradition it is reported that the Prophet himself had a non-Muslim wife. However, the campaign to propagate Christianization which had been tirelessly carried out by well-organized missionary organizations was reported to  have successfully christianized segments of the Indonesian population especially in the heathen hinterland and among outer island tribes. Given the circumstances, the Muslim leaders and ulama perceived inter-religious marriage as a hidden Christianization. The increasing incidence of inter-religious marriage raised the concern of the Indonesian Council of Ulama. Responding to this problem, in June 1, 1980 the Council issued a fatwa which explicitly prohibits a Muslim to marry a non-Muslim. Even though the position adopted by the fatwa was quite a radical departure from the prevalent opinion in classical fiqh text, this legal opinion is still within the permissible frame of Islamic legal theory of maslahah (beneficial theory).  This legal theory is encapsulated in the Syafi’i school’s legal maxim stating that “Dar’u al-mafâsid muqaddam ‘alâ jalb al-masâlih” (Preference is given to the prevention of harm than toattainment of benefit)